2020
DOI: 10.1097/mpg.0000000000002599
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact and Prognostic Factors of Functional Dyspepsia in Children

Abstract: Objectives: Functional dyspepsia (FD) is a functional abdominal pain disorder. There is paucity of data on the economic impact of FD in children. Primary aim of our study was to estimate annual evaluation cost (“diagnosis and visit” cost) and secondary aim was to identify potential prognostic factors of FD in children. Methods: Out of the 136 patients 86 met inclusion criteria and were divided into 2 clinical groups: Complete Improvement Group (CIG-30 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
19
0
3
Order By: Relevance
“…5 In the USA alone, social and economic costs are estimated to be approximately $18.4 billion/year for adults and $5.79 billion/year for children. 4,6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the USA alone, social and economic costs are estimated to be approximately $18.4 billion/year for adults and $5.79 billion/year for children. 4,6…”
Section: Introductionmentioning
confidence: 99%
“…5 In the USA alone, social and economic costs are estimated to be approximately $18.4 billion/year for adults and $5.79 billion/year for children. 4,6 Functional dyspepsia is a chronic GI disorder defined by upper abdominal symptoms originating from the gastroduodenal region and characterized by the absence of morphological disease on routine investigations, including upper GI endoscopy. [1][2][3]7,8 The Rome IV criteria define dyspepsia as any combination of four specific symptoms: (I) postprandial filling; (II) early satiety; (III) epigastric pain; and (IV) epigastric burning.…”
Section: Introductionmentioning
confidence: 99%
“…Lane and colleagues 8 found that adding endoscopy to the analysis causes a 9-fold increase in costs. Mani and colleagues 31 found cost of evaluation to be $5.79 billion annually when treating children with functional dyspepsia. An 11-country survey in Europe found 62% of responders utilized laboratory tests and endoscopy to diagnose IBS, and 29% referred IBS patients to a specialist.…”
Section: Discussionmentioning
confidence: 99%
“…The costs of care of pediatric AP-FGIDs are significant and continue to rise [3][4][5]. These costs are particularly high in patients who are unresponsive or only partially responsive to treatment [6]. In addition, up to 30% of AP-FGIDs persist into adulthood, where the health care costs of IBS alone are over USD 20 billion per year [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there are currently no evidence-based pediatric practice guidelines to direct care of these patients. There is a critical need to assess treatment in terms of value or, in other words, the outcomes relative to costs [6,7]. This could be accomplished through multi-site quality improvement projects provided there is sufficient variability in outcomes and/or costs among centers.…”
Section: Introductionmentioning
confidence: 99%